EXPLORATING THE MAIN ACTORS IN THE ACTUALIZATION OF THE VALUE OF SOCIAL JUSTICE DURING THE COVID-19 PANDEMIC - Yudha Dwi Nugraha (Academy of Education Journal, 2022)
The World Health Organization (WHO) issued a physical distancing policy that inspires people to engage in contactless activities and ultimately causes a decrease in income for most Indonesians, MSME in particular. Government authorities in various countries have also adopted lockdown policies to prevent the spread of covid-19. This research focuses on describing the actualization of the value of social justice during the Covid-19 pandemic, the constraints on the actualization of the value of social justice during the Covid-19 pandemic, and solutions that can be used to accelerate the actualization of the value of social justice during the Covid-19 pandemic. This research used a qualitative approach with descriptive methods. Data obtained through literature study techniques. The results showed that there were three main actors in the actualization of the value of social justice during the Covid-19 pandemic, namely government, society, and individuals.